Semi‐intensive shrimp farms as experimental arenas for the study of predation risk from falcons to shorebirds. Issue 19 (7th September 2021) - Basso, Enzo; Drever, Mark C.; Fonseca, Juanita; Navedo, Juan G.
Abstract: Varying environmental conditions and energetic demands can affect habitat use by predators and their prey. Anthropogenic habitats provide an opportunity to document both predation events and foraging activity by prey and therefore enable an empirical evaluation of how prey cope with trade‐offs between starvation and predation risk in environments of variable foraging opportunities and predation danger. Here, we use seven years of observational data of peregrine falcons Falco peregrinus and shorebirds at a semi‐intensive shrimp farm to determine how starvation and predation risk vary for shorebirds under a predictable variation in foraging opportunities. Attack rate (mean 0.1 attacks/hr, equating 1 attack every ten hours) was positively associated with the total foraging area available for shorebirds at the shrimp farm throughout the harvesting period, with tidal amplitude at the adjacent mudflat having a strong nonlinear (quadratic) effect. Hunt success (mean 14%) was higher during low tides and declined as the target flocks became larger. Finally, individual shorebird vigilance behaviors were more frequent when birds foraged in smaller flocks at ponds with poorer conditions. Our results provide empirical evidence of a risk threshold modulated by tidal conditions at the adjacent wetlands, where shorebirds trade‐off risk and rewards to decide to avoid or forage at the shrimp farm (a potentially dangerous habitat) depending on their need to meet daily energy requirements. We propose that semi‐intensive shrimp farms serve as ideal "arenas" for studying predator–prey dynamics of shorebirds and falcons, because harvest operations and regular tidal cycles create a mosaic of foraging patches with predictable food supply. In addition, the relatively low hunt success suggests that indirect effects associated with enhanced starvation risk are important in shorebird life‐history decisions. Abstract : Shrimp farms can serve as ideal arenas for the study of trade‐offs between starvation and predation risk in shorebird populations at coastal areas during the nonbreeding season.